Enhancement of the advanced Na storage performance of Na3V2(PO4)3 in a symmetric sodium full cell via a dual strategy design. Issue 17 (12th April 2019) - Li, Wei; Yao, Zhujun; Zhong, Yu; Zhou, Cheng-ao; Wang, Xiuli; Xia, Xinhui; Xie, Dong; Wu, Jianbo; Gu, Changdong; Tu, Jiangping
Abstract : An HP-NVP@SC composite combining a highly porous structure with a sulfur-doped carbon layer demonstrates superior Na-ion storage performance with high capacities and excellent cycling stability. Abstract : The exploration of advanced cathode materials with high electron conductivity and sodium-ion diffusion coefficient is of great significance for the further development of sodium-ion batteries. To improve the sodium-ion storage performance, herein, a dual strategy design involving the combination of a highly porous Na3 V2 (PO4 )3 structure and a superior ionic/electronic conductive sulfur-doped carbon layer (HP-NVP@SC) is presented; a number of advantageous qualities, including large surface area, numerous active sites and a well-developed diffusion pathway, are exhibited by this composite. Notably, the HP-NVP@SC composite exhibits a superior rate performance (116.5 mA h g −1 at 1C; 95 mA h g −1 at 30C) and long-term cycling stability with 91% capacity retention after 2500 charge/discharge cycles at 20C. Specifically, the symmetric full cell assembled using the HP-NVP@SC composite as both a cathode and an anode also shows remarkable rate capability and notable cycling life with the high energy density of 164 W h kg −1 at 1C. This dual strategy may inspire more research towards the construction of high-performance sodium-ion batteries.